2016
DOI: 10.1039/c5ta04314j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of (Ga1−xZnx)(N1−xOx) nanocrystals with a wide range of compositions

Abstract: We describe the synthesis and characterization of wurtzite (Ga 1Àx Zn x )(N 1Àx O x ) nanocrystals with a wide range of compositions and a focus on properties relevant for solar fuel generation. (Ga 1Àx Zn x )(N 1Àx O x ), a solid solution of GaN and ZnO, is an intriguing material because it exhibits composition-dependent visible absorption even though the parent semiconductors absorb in the UV. When functionalized with co-catalysts, (Ga 1Àx Zn x )(N 1Àx O x ) is also capable of water splitting under visible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 59 publications
4
67
0
Order By: Relevance
“…A mixture of the orthorombic LiGaO2 and wurtzite GaN was determined for ZG1-2 ( Figure 4c). This result suggested that the nitridation of single-phase ZnGa2O4 does not produce an oxynitride compound [2]. The loss of zinc may cause a reduction of ZnO to metallic Zn during the nitridation [1,11,16,17], suggesting that the presence of zinc oxide is required to efficiently synthsize (Ga1-xZnx)(N1-xOx).…”
Section: Formationof Zinc Gallium Oxynitride (Ga1-xznx)(n1-xox)mentioning
confidence: 82%
See 1 more Smart Citation
“…A mixture of the orthorombic LiGaO2 and wurtzite GaN was determined for ZG1-2 ( Figure 4c). This result suggested that the nitridation of single-phase ZnGa2O4 does not produce an oxynitride compound [2]. The loss of zinc may cause a reduction of ZnO to metallic Zn during the nitridation [1,11,16,17], suggesting that the presence of zinc oxide is required to efficiently synthsize (Ga1-xZnx)(N1-xOx).…”
Section: Formationof Zinc Gallium Oxynitride (Ga1-xznx)(n1-xox)mentioning
confidence: 82%
“…Oxynitride semiconductor is one of the intriguing materials for energy conversion [1][2][3]. Domen et al for the first time reported on the development of GaN:ZnO solid solution for visible-light driven water splitting [4].…”
Section: Introductionmentioning
confidence: 99%
“…All the photocurrents of the Ga 1-x Zn x N 1-x O x solid solutions, including the literature data reported thus far, were converted into the value of 1.23 V of an NHE at a pH of 0 and plotted. The photocurrent characteristics of Ga 1-x Zn x N 1-x O x solid solutions have been reported for films formed by the electrophoresis method12 and the doctor blade method16. The photocurrents reported thus far are on the several μA/cm 2 level.…”
Section: Resultsmentioning
confidence: 99%
“…This result led researchers to consider synthesis methods capable of further increasing the dissolved amount of ZnO. Syntheses under high pressure14, using nanoparticulate raw material1516, using a Zn/Ga/CO 3 layered double hydroxide1718, and using a ZnGaO precursor1920 were studied, and solid solutions with X = 0.8 to 0.9 were synthesized. In all of the synthesis methods, the band gap tends to decrease with the amount of ZnO added.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Currently,t he ZnO:GaN solid solutionsa re alwaysp repared by nitridation of the mixed oxide commonly by co-precipitation and more recently by sol-gelb ased processes;h owever, so far alwaysu nder NH 3 flow as nitrification agent. [9,10] Commons tarting materials are the single or mixed oxides, [11,12,13,14] hydroxide, [15] gel-like precursors, [16] Zn/Ga/CO 3 layered double hydroxides [17] or ammonolysis of amorphous precursors. [18] Even when urea was used as nitrogen source, the synthesis required the preparation of hydroxides, which were treated at 900 8Cu nder ammonia flow.…”
Section: Introductionmentioning
confidence: 99%